Eccentric knee flexor strength of professional football players with and without hamstring injury in the prior season - Breno Ribeiro-Alvares, J.; dos Santos Oliveira, G.; de Lima-E-Silva, F. X.; Manfredini Baroni, B. (European Journal of Sport Science, 2021)
Both injury history and eccentric knee flexor strength have been associated with risk of football players sustaining hamstring strain injury (HSI). However, it remains unclear whether football players who sustained HSIs in the prior season present persistent eccentric strength deficits. Therefore, the aim of the present study was to verify the eccentric knee flexor strength of professional male football players with and without history of HSI in the prior season. This case-control study assessed 210 professional male football players from 10 Brazilian clubs: 182 included in the control group and 28 in the previously injured group. Players from the injured group had suffered unilateral HSI in the prior season. We measured the knee flexors peak force during the Nordic hamstring exercise and calculated the between-limb asymmetry. Groups were similar for age, body mass and height (p > 0.05). Control group had similar strength values between left and right limbs (376.29 ± 61.77 N vs. 380.28 ± 61.77 N; p = 0.27; d = 0.06), while the previously injured limb was weaker than the contralateral uninjured limb in the injured group (350.87 ± 60.79 N vs. 385.75 ± 63.49 N; p < 0.01; d = 0.56). Thirty-seven percent of players in the control group and 50% in the injured group presented between-limb asymmetry >10%. This study demonstrates that players with history of HSI in the prior season present reduced eccentric knee flexor strength in the injured limb, but half of them have between-limb asymmetry within the most commonly adopted benchmark value of 10%.